Dysnatremia is associated with increased risk of all-cause mortality within 365 days post-discharge in patients with atrial fibrillation without heart failure: A prospective cohort study - Zhou, Yan; Lin, Dong; Wu, Shiwan; Xiao, Jiaxin; Yu, Min; Xiao, Zhongbo; Wu, Muli; Chen, Zhisheng; Tian, Cuihong; Chen, Rongbing; Chen, Yequn; Tan, Xuerui (Frontiers in Cardiovascular Medicine, 2022)
Abstract Aim: To evaluate the association between serum sodium concentrations at hospital admission and all-cause mortality within 365 days post-discharge in atrial fibrillation (AF) patients without heart failure (HF). Methods: The prospective cohort study enrolled 1446 AF patients, without HF, between November 2018 and October 2020. Follow-up was performed, at 30-, 90-, 180-, and 365-days after enrollment, through outpatient visits or telephone interviews. All-cause mortality was estimated in three groups according to serum sodium concentrations: hyponatremia (<135 mmol/L), normonatremia (135-145 mmol/L) and hypernatremia (>145 mmol/L). We estimated the risk of all-cause mortalities using univariable and multivariable Cox proportional hazards models, with normonatremia as the reference. Results: The all-cause mortalities in hyponatremia, normonatremia, and hypernatremia were 20.6%, 9.4% and 33.3% within 365 days post-discharge, respectively. In the univariable analysis, hyponatremia (HR: 2.19, CI 1.50-3.20) and hypernatremia (HR: 4.03, CI 2.32-7.02) increased the risk of all-cause mortality. The HRs for hyponatremia and hypernatremia were 1.55 (CI 1.05-2.28) and 2.55 (CI 1.45-4.46) after adjustment for age, diabetes mellitus, loop diuretics, antisterone, antiplatelet drugs, and anticoagulants in AF patients without HF. The association between serum sodium concentrations and HRs of all-cause mortality was U-shaped. Conclusion: Dysnatremia at hospital admission was an independent factor for all-cause mortality in AF patients without HF within 365 days post-discharge.